The effect of two types of moderate and high intensity aerobic exercise on the levels of monocarboxylate transporters type 2 and 4 in the cortex and striatum of healthy and stroke Wistar rats models - Mosayeb Rastegar Harooki; Rasoul Rezaei; Javad Nemati; Mohsen Salesi; Mohammad Hemmatinafar (فیزیولوژی ورزش و فعالیت بدنی)
Background and Purpose: Monocarboxylate transporters type 2 and 4 (MCT2 and MCT4) levels are high in brain tissue, which can be useful in postponing fatigue during exercise by transporting lactate in the brain.Therefore, the purpose of this research was to investigate the effects of two types of aerobic exercise with different intensities on the amounts of MCT2 and MCT4 in the cortex and striatum of healthy and stroke Wistar rats models.Materials and Methods: In the present research 60 male Wistar rats (8 weeks old) were randomly divided into ten groups of control and healthy moderate intensity continuous training (MICT) and high intensity interval training (HIIT) of  24 and 72-hour stroke (6 rats in each group). The MICT and HIIT protocol consisted of three parts: warm-up, main exercise and cool-down. The training period lasted for 4 weeks, 5 sessions per week and each session lasted 32 minutes. The MICT protocol was performed at an intensity corresponding to 70% of the maximum speed and the HIIT protocol at an intensity of 85-90% of the maximum speed. Stroke was induced by blocking the carotid artery. The content of MCT2 and MCT4 was measured by Western blot technique in the cortex and striatum of the brain. Data analysis were performed by using one-way ANOVA and Tukey's post hoc tests in SPSS software version 29 and GraphPad Prism version 2.2.10 at a significance level of p≤0.05.Results: Significant differences in the content of cortical tissue MCT2 (p=0.59)  and the content of striatum tissue MCT2 (p=0.66) and MCT4 (p=0.22) were not found after four weeks of MICT and HIIT in healthy and stroke groups. However, MCT4 content in cortical tissue showed a significant difference after 72 hours of stroke (p<0.05). Tukey's post-hoc test for MCT4 content showed a significant difference between the 72-hour stroke HIIT groups compared to the 72-hour stroke MICT (p=0.02), 72-hour stroke control (p=0.04), 24-hour stroke HIIT (p=0.01), 24-hour stroke MICT (p=0.009), 24-hour stroke control (p=0.003), and MICT (p=0.02) groups.Conclusion: It seems that MICT and HIIT do not have a significant effect on the content of MCT2 and MCT4 in the brain. However, in the cortical tissue, a significant difference was observed in the MCT4 of the HIIT group with a 72-hour stroke compared to the other groups, and this could indicate the withdrawal of lactate by the MCT4 72 hours after the stroke and recovery.